Emotion regulation difficulties in binge eating disorder with and without the overvaluation of weight and shape. (30th November 2016) - Harrison, Carmel; Mitchison, Deborah; Rieger, Elizabeth; Rodgers, Bryan; Mond, Jonathan
Abstract: The objective of this study was to examine the relationship between overvaluation of weight/shape ('overvaluation') and emotion regulation (ER) difficulties among women with binge eating disorder (BED) symptoms. Four groups of women were recruited from a community-based sample and compared on ER difficulties: individuals with probable BED with (n=102) and without (n=72) overvaluation, and non-binge eating obese (n=40) and healthy-weight (n=40) control participants. Data for patients with a formal diagnosis of BED receiving treatment from a previous study were included for numerical comparative purposes. Women with probable BED and overvaluation reported significantly greater ER difficulties than all other groups and had similar levels of ER difficulties to BED patients. Women with probable BED in the absence of overvaluation were comparable to the obese control group on total ER difficulties and the majority of the ER difficulties subscales. The findings provide further evidence for the clinical significance of overvaluation among individuals with BED symptomatology. BED in the absence of overvaluation does not appear to align with current models of the disorder in which ER difficulties are viewed as a core etiological mechanism. Further research is needed to elucidate the status of this presentation. Highlights: Women with BED and overvaluation reported more emotion regulation difficulties. BED without overvaluation and obese controls displayed similar emotion regulation. Findings emphasize the importance of overvaluation in diagnostic criteria for BED.